Dynamics of tandemly repeated DNA sequences during evolution of diploid and tetraploid botiid loaches (Teleostei: Cobitoidea: Botiidae) - Sember, Alexandr (PLoS One, 2018)
Polyploidization has played an important role in the evolution of vertebrates, particularly at the base of Teleostei–an enormously successful ray-finned fish group with additional genome doublings on lower taxonomic levels. The investigation of post-polyploid genome dynamics might provide important clues about the evolution and ecology of respective species and can help to decipher the role of polyploidy per se on speciation. Few studies have attempted to investigate the dynamics of repetitive DNA sequences in the post-polyploid genome using molecular cytogenetic tools in fishes, though recent efforts demonstrated their usefulness. The demonstrably monophyletic freshwater loach family Botiidae, branching to evolutionary diploid and tetraploid lineages separated >25 Mya, offers a suited model group for comparing the long-term repetitive DNA evolution. For this, we integrated phylogenetic analyses with cytogenetical survey involving Giemsa- and Chromomycin A(3) (CMA(3))/DAPI stainings and fluorescence in situ hybridization with 5S/45S rDNA, U2 snDNA and telomeric probes in representative sample of 12 botiid species. The karyotypes of all diploids were composed of 2n = 50 chromosomes, while majority of tetraploids had 2n = 4x = 100, with only subtle interspecific karyotype differences. The exceptional karyotype of Botia dario (2n = 4x = 96) suggested centric fusions behind the 2n reduction. Variable patterns of FISH signals revealed cases of intraspecific polymorphisms, rDNA amplification, variable degree of correspondence with CMA(3)(+) sites and almost no phylogenetic signal. In tetraploids, either additivity or loci gain/loss was recorded. Despite absence of classical interstitial telomeric sites, large blocks of interspersed rDNA/telomeric regions were found in diploids only. We uncovered different molecular drives of studied repetitive DNA classes within botiid genomes as well as the advanced stage of the re-diploidization process in tetraploids. Our results may contribute to link genomic approach with molecular cytogenetic analyses in addressing the origin and mechanism of this polyploidization event.